Development of a L‐cysteine Sensor Based on Thallium Oxide Coupled Multi‐walled Carbon Nanotube Nanocomposites with Electrochemical Approach. Issue 3 (7th January 2022) - Musarraf Hussain, Mohammad; Asiri, Abdullah M.; Uddin, Jamal; Marwani, Hadi M.; Rahman, Mohammed M.
Abstract: Here, nanocomposites of thallium oxide doped multi‐walled carbon nanotube (Tl2 O MWCNT NCs) were prepared by utilizing a wet‐chemical method (WCM) in an alkaline phase at low temperature. Different optical procedures (FTIR: Fourier Transform Infra‐Red Spectroscopy, XRD: Powder X‐ray diffraction, FESEM: Field‐Emission Scanning Electron Microscopy, XEDS: X‐ray Electron Dispersive Spectroscopy, TEM: Tunneling Electron Microscopy, and XPS: X‐ray photoelectron spectroscopy) were used to fully characterize (optical, structural, crystalline, morphological, and elemental etc.) of the prepared Tl2 O MWCNT NCs. Modification of the thin‐layer with NCs onto glassy carbon electrode (GCE) is prepared and applied for the selective and sensitive enzyme‐free detection of L‐cysteine by an electrochemical approach. Using a reliable current‐voltage approach, analytical sensing indexes such as sensitivity, LDR, LOD, LOQ, durability, and interference were assessed by fabricated sensor probe (GCE/Tl2 O MWCNT NCs/CPM) in selective detection of L‐cysteine at room temperature, whereas nafion was used as conducting polymer matrix (CPM) during the fabrication of GCE with NCs. L‐cysteine calibration plot was found to be linear over an extensive range of concentration. The calibration curve was used to calculate the sensing parameters such as sensitivity (316.46 pAμM −1 cm −2 ), LOD down to (∼18.90±1.89 pM), and LOQ (63.0 pM) of the prepared sensor. The use of a simple WCM to validate the Tl2 O.MWCNT NCs is a good approach for developing a NCs‐based sensor for enzyme‐free biomolecule identification and detection in the biomedical and health care fields in a broad scale. This proposed sensor (GCE/Tl2 O MWCNT NCs/CPM) is used to detect selective L‐cysteine in real biological samples such as human, mouse, and rabbit serum and found acceptable and satisfactory results. Abstract : An electrochemical approach for the selective and sensitive detection of L‐cysteine is reported. The devopled sensor is based on a thallium oxide (Tl2 O) coupled multi‐walled carbon nanotube nanocomposite by electrochemical approach.